Ultrasonic Velocity, Viscosity and Density of LiCl in Aqueous Solutions of Alcohols at 303.15 K - Arbad, B.R.; C.S. Patil, Mrs.; Shankarwar, A.G. (Asian Journal of Chemistry, 2010)
Densities (ρ), ultrasonic velocities (U) and relative viscosity (ηr) of lithium chloride in 20% ethanol + water mixtures have been measured as a function of electrolyte concentration at 303.15 K temperature. The experimental values of ρ and U are used to calculate isentropic compressibility (φk), intermolecular free length (Lf), relative association (RA), and apparent molar volume (φv).The derived parameters have been used to interpret the solvent-solvent, ion-solvent and solute-solvent interactions.